Neurochemistry of the hippocampus in patients with obsessive-compulsive disorder - Atmaca, Murad; Yildirim, Hanefi; Ozdemir, Huseyin; Koc, Mustafa; Ozler, Sinan; Tezcan, Ertan (Wiley-Blackwell Publishing, Inc, 2009)
Aim: To date, despite possible neuroanatomical importance, no magnetic resonance spectroscopy (MRS) study on hippocampus has been performed in obsessive-compulsive disorder (OCD). The purpose of the present study was therefore to compare hippocampal chemicals in patients with OCD with those in healthy subjects with no psychopathology. Methods: Eighteen patients meeting DSM-IV criteria for OCD and 18 healthy controls were studied. The patients and controls underwent proton magnetic resonance spectroscopy ((1)H-MRS), and measures of N-acetyl-l-aspartate (NAA), choline (CHO), and creatine (CRE) in hippocampal regions were obtained. Results: Both NAA/CRE and NAA/CHO ratios in the hippocampus in patients with OCD were reduced relative to healthy controls. The ANOVA showed a near-significant effect of diagnosis for NAA/CRE and a significant effect for NAA/CHO, but the ANOVA did not show any significant effect even at a trend level for CHO/CRE. No main effect of hemisphere was found for any metabolite ratio. Conclusions: The presence of neuronal degeneration is suggested in OCD. Future longitudinal neuroimaging and neuropsychological studies with larger patient samples are warranted in order to confirm these preliminary findings to better characterize the relevance of neurochemical abnormalities in hippocampus in the pathophysiology of OCD.
Keywords: choline; magnetic resonance spectroscopy; N-acetylaspartate; obsessive-compulsive disorder; spectroscopy